2009
DOI: 10.1016/j.jvs.2008.12.066
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound velocity criteria for renal in-stent restenosis

Abstract: The current DUS criteria for native renal arteries may overestimate the degree of angiographic ISR due to changes in compliance. We recommend that DUS laboratories make adjustments in PSV and RAR obtained by DUS when monitoring the patency of renal stents for ISR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(57 citation statements)
references
References 28 publications
1
52
0
4
Order By: Relevance
“…No consensus has been reached on the appropriate criteria after renal stenting, however Chi et al have suggested that the PSV criteria be raised to Ͼ395 cm/s and the renal aortic ratio to Ͼ5.1. 13 Another concern of repeat procedures on the renal artery is the long-term effect on renal function. We are unaware of any reported data that provide the natural history of untreated severe in-stent renal artery stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…No consensus has been reached on the appropriate criteria after renal stenting, however Chi et al have suggested that the PSV criteria be raised to Ͼ395 cm/s and the renal aortic ratio to Ͼ5.1. 13 Another concern of repeat procedures on the renal artery is the long-term effect on renal function. We are unaware of any reported data that provide the natural history of untreated severe in-stent renal artery stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…4 These findings have been extensively studied and confirmed in patients with carotid stents, [5][6][7][8][9] and similar observations have also been noted in patients with renal stenting. 10 Previously, we reported a relatively high incidence of ISS after percutaneous transluminal angioplasty/stenting of the SMA and CA, and several authorities felt that might be attributed to overestimation of the stenosis because we used the same duplex velocities that we use for native arteries. 11 To the best of our knowledge, there has only been one study published on this subject, and it concluded that the duplex velocity criteria used to determine native SMA stenoses overestimated stenoses in stented SMA arteries.…”
mentioning
confidence: 99%
“…Follow-up to 24 months showed that these clinical improvements were maintained and all monthly duplex mapping examinations showed criteria for in-stent stenosis of 50-70% ( Figures 5 and 6), according to the criteria described by Chi et al 13 (PSV from 225 to 315 cm/s and RAR from 3.12 to 4.66), up to 2014 (Figure 7).…”
Section: Part II -What Was Donementioning
confidence: 63%